APPLICATION OF BLENDED LEARNING MODEL FLIPPED CLASSROOM IN BUSINESS FEASIBILITY STUDY COURSES: Case Study on Students of STKIP Development Economic Education Study Program in Indonesia during the Covid-19 Period - Hamran Hamran; Eka Adnan Agung (International Journal of Economy, Education and Entrepreneurship, 2022)
This research is descriptive. We intend to conduct the research presented here. At the STKIP Development Indonesia Economic Education Study Program in the Even Semester of the 2021/2022 Academic Year. The population in this study were students of the 2019 Economics Education Study Program who were programming a business feasibility study course. The samples of this study were students of class 6/D, amounting to 33 active people. Data collection techniques in this study are observation and questionnaires. The purpose of this study is to find out and describe data regarding student responses to the application of the blended learning model of the flipped classroom. The observation sheet consists of perceiving the teaching and learning process, organizing the teaching and learning process, and evaluating the teaching and learning process. The student response questionnaire consists of interest, learning awareness, and motivation. Data analysis in this study was used to describe student responses after participating in the teaching and learning process. According to the findings, the student's reactions to implementing the blended learning model in the flipped classroom fell into the "Good."